2018
DOI: 10.3168/jds.2018-14776
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Technological and seasonal variations of vitamin D and other nutritional components in donkey milk

Abstract: Vitamin D is an essential nutrient that plays a crucial role in calcium homeostasis and bone metabolism and also acts as a hormone. Although several studies on the content of vitamin D in bovine milk have been conducted, little information is available regarding donkey milk. In the context of the nutritional assessment of donkey milk, the aim of this study was to assess the vitamin D content in donkey milk and its chemical profile, with particular reference to seasonal and technological modifications after pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…Finally, it should be noted that the concentration of vitamin B6 has been determined for the first time in donkey milk. Previous works showed that donkey milk has hypoallergenic properties [44], possesses proteins with antimicrobial activity [10], has a considerable amount of vitamin C [19], vitamin D [23], nucleosides and nucleotides with sleep-inducing properties [45]. This study has demonstrated the presence of essential vitamins in donkey milk and confirmed that this milk is suitable for feeding children affected by CMPA that cannot be breastfed, but also that it can be appropriated for the elder people.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Finally, it should be noted that the concentration of vitamin B6 has been determined for the first time in donkey milk. Previous works showed that donkey milk has hypoallergenic properties [44], possesses proteins with antimicrobial activity [10], has a considerable amount of vitamin C [19], vitamin D [23], nucleosides and nucleotides with sleep-inducing properties [45]. This study has demonstrated the presence of essential vitamins in donkey milk and confirmed that this milk is suitable for feeding children affected by CMPA that cannot be breastfed, but also that it can be appropriated for the elder people.…”
Section: Discussionsupporting
confidence: 72%
“…In another work, the vitamin D content in DM was determined, the concentration resulted to be 0.042 µM for the vitamin D 2 , and 0.016 µM for the vitamin D 3 . These values were higher if compared to those found in human milk and bovine milk (0.008 µM) [23]. The same authors showed that the vitamin D content has a seasonal variation, since it is more concentrated in summer compared to winter, probably because of the greater sun exposure of the animals.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Pieszka et al [36] reviewed the level of fat-soluble vitamins (A, D, E) in mare milk and found them consistent with values reported for bovine milk. Donkey milk is reported to contain a higher level of vitamin D [37] but it displays very low contents of vitamins A and E, as probably related to the low-fat content [28]. Among the water-soluble vitamins, pyridoxine, pantothenic acid, cobalamin, and vitamin C have so far been detected at high levels only in mare milk [28,36].…”
Section: Equine Milk Compositional and Nutritional Featuresmentioning
confidence: 99%
“…Compared to ruminant milk, donkey milk has on average lower fat, protein and casein content, a smaller average diameter of fat globules, lower quantity of saturated fatty acids, and a higher C18:3 n3 content of lactose (71.2 g/l) and vitamin D (Martini et al 2018a(Martini et al , 2018b.…”
Section: Introductionmentioning
confidence: 99%